Hepatic venous pressure gradient-guided laparoscopic splenectomy and pericardial devascularisation versus endoscopic therapy for secondary prophylaxis for variceal rebleeding in portal hypertension (CHESS1803): study protocol of a multicenter randomised controlled trial in China - Shao, Ruoyang (BMJ Open, 2020)
INTRODUCTION: Gastro-oesophageal variceal bleeding is one of the most common and severe complications with high mortality in cirrhotic patients who developed portal hypertension. Hepatic venous pressure gradient (HVPG) is a globally recommended golden standard for the portal pressure assessment and an HVPG ≥16 mm Hg indicates a higher risk of death and rebleeding. This study aims to compare the effectiveness and safety of splenectomy and pericardial devascularisation (laparoscopic therapy) plus propranolol and endoscopic therapy plus propranolol for variceal rebleeding in cirrhotic patients with HVPG between 16 and 20 mm Hg. METHODS AND ANALYSIS: This is a multicenter, randomised, controlled clinical trial. Participants will be 1:1 assigned randomly into either laparoscopic or endoscopic groups. Forty participants whose transjugular HVPG lies between 16 and 20 mm Hg with a history of gastro-oesophageal variceal bleeding will be recruited from three sites in China. Participants will receive either endoscopic therapy plus propranolol or laparoscopic therapy plus propranolol. The primary outcome measure will be the occurrence of gastro-oesophageal variceal rebleeding. Secondary outcome measures will include overall survival, occurrence of hepatocellular carcinoma, the occurrence of venous thrombosis, the occurrence of adverse events, quality of life and tolerability of treatment. Outcome measures will be evaluated at baseline, 12 weeks, 24 weeks, 36 weeks, 48 weeks and 60 weeks. Multivariate COX regression model will be introduced for analyses of occurrence data and Kaplan-Meier analysis with the log-rank test for intergroup comparison. ETHICS AND DISSEMINATION: Ethical approval was obtained from all three participating sites. Primary and secondary outcome data will be submitted for publication in peer-reviewed journals and widely disseminated. TRIAL REGISTRATION NUMBER: NCT03783065; Pre-results. TRIAL STATUS: Recruitment for this study started in December 2018 while the first participant was randomised in January 2019. Recruitment is estimated to stop in October 2019.